Compensative Resistance to Erastin-Induced Ferroptosis in GPX4 Knock-Out Mutants in HCT116 Cell Lines - Malgorzata Adamiec-Organisciok; Magdalena Wegrzyn; Lukasz Cienciala; Damian Sojka; Joanna Nackiewicz; Magdalena Skonieczna (MDPI AG, 2023)
Ferroptosis results from the accumulation of oxidized and damaged lipids which then leads to programmed cell death. This programmed process is iron-dependent, and as a fundamental biological process, plays a crucial role in tissue homeostasis. The ferroptosis molecular pathway depends on self-regulatory genes: GPX4; TFRC; ACSL4; FSP1; SLC7A11, and PROM2. Some of them were considered here as ferro-sensitive or ferro-resistance markers. We examined the impact of GPX4 gene knock-out, using the CRISPR/Cas-9 technique, on ferroptosis induction in the HCT116 colorectal cancer cell line. The results confirmed that cells lacking the GPX4 gene (GPX4 KO) should be more susceptible to ferroptosis after erastin treatment. However, the decrease in cell viability was not as significant as we initially assumed. Based on the lipid peroxidation markers profile and RT-qPCR gene expression analysis, we revealed the activation of an alternative antioxidant system supporting GPX4 KO cells, mostly for cellular ferroptotic death avoidance. Increased expression of FSP1 and PRDX1 genes in knock-out mutants was associated with their function-recognized here as ferroptosis suppressors. For such reasons, studies on the role of GPX4 and other crucial genes from the ferroptotic pathway should be explored. Despite promising prospects, the utilization of ferroptosis mechanisms in cancer therapy remains at the stage of experimental and in vitro preclinical studies.